(untitled) (Research, Society and Development, 2022)
Objective: to analyze the factors associated with the development of pressure ulcers in heels of patients undergoing cardiac surgery. Method: quantitative analysis of data extracted from a self-controlled randomized clinical trial. Data collection of the randomized clinical trial occurred from March 2019 to February 2020. 268 patients were screened for eligibility, and after applying the selection criteria, 135 patients were included. A total of 91 subjects were analyzed, referring to the cardiac specialty. The data were statistically analyzed with the help of the Statistical Package for the Social Sciences program version 21. Results: Of the 91 research participants, 49 (53.8%) developed PUs. Regarding the association of factors with PU development, hypothermia in the immediate postoperative period was found to be significantly associated (p<0.001). Of the 91 patients analyzed, 26 (28.6%) presented hypothermia in the immediate postoperative period and developed PUs. Conclusion: hypothermia in the immediate postoperative period is a factor associated with the development of calcaneal PUs in individuals undergoing cardiac surgery.